Hubungan tingkat depresi dan kualitas hidup yang diukur menggunakan HRQol pada pasien hipertensi di Puskesmas Mantrijeron, Yogyakarta - Dwy Rahmawati; Solikhah Solikhah (Universitas Ahmad Dahlan, 2022)
Globally, hypertension remains a public health issue. Hypertension is a risk factor for other serious diseases such as heart disease. The inability to control blood pressure in some hypertensive patients can lead to depression and anxiety, lowering their quality of life. The purpose of this study was to see if there was a link between depression and quality of life as measured by HRQoL in hypertensive patients at the Mantrijeron Health Center. The study design was cross-sectional and the method used was analytic observational. The study's findings revealed that 323 patients (85.90%) had severe depression, with 349 (92.82%) having poor quality of life. According to the findings of the bivariate analysis, there is a link between depression and quality of life (95% CI:69,499 - 1401,397). The level of depression was related to occupation (95% CI: 0.209 - 20,096). Furthermore, income was related to quality in hypertensive patients (95% CI: 0.177 - 0.867). According to the findings of this study, the level of depression is related to the quality of life in hypertensive patients. Stress management, possibly through education, should be integrated into overall hypertension management to maintain patients' mental health.